Stroke survivors' perceptions of participating in a high repetition arm training trial early after stroke. Issue 20 (25th September 2022) - Hammerbeck, Ulrike; Hargreaves, Mary; Hollands, Kristen L.; Tyson, Sarah
Abstract: Purpose: The study explored the acceptability of high repetition arm training as part of a randomised controlled trial, early after stroke, when fatigue levels and emotional strain are often high. Materials and methods: 36 sub-acute stroke survivors (61 years+/-15) attended for assessment sessions at 3, 6, and 12 weeks after stroke. Individuals were randomised to receive 6 high repetition arm training sessions between 3 and 6 weeks (intervention) or the control group. Semi-structured interviews were conducted at trial completion. Interview transcripts were analysed through framework analysis conducted independently by 2 researchers. Results: Stroke survivors participated despite high levels of fatigue because they hoped for personal benefit or to potentially benefit future patients. Benefits reported from participation included physical improvements, psychological benefit, improved understanding of their condition as well as a feeling of hope and distraction. The arm training at three weeks after stroke, aiming for 420 movement repetitions was not considered to be too intensive or too early, and most individuals felt lucky to have been, or would have preferred to be in the early training group. Conclusion: High repetition arm training early after stroke was acceptable to participants. Study participation was generally viewed as a positive experience, suggesting that early intervention may not only be physically beneficial but also psychologically. Implications for rehabilitation: Stroke survivors report that high repetition arm training early after stroke is acceptable. Participation in rehabilitation research early after stroke provides stroke survivors with hope and meaning despite the high prevalence of fatigue. Complex information needs to be repeated and provided in a number of formats early after stroke.